Magnitude, associated risk factor and awareness of predisposing factors, treatment, and prevention of overweight/obesity among adults in North Wollo zone, Northeast Ethiopia - Belete, Aychew Kassa; Asefa, Yeshiwas Jemberu; Taye, Birhan Ambachew (Frontiers in Nutrition, 2025)
AimBad eating habits and an insufficient amount of body activity can contribute to obesity and overweight. This study looked at the prevalence, related risk factors, awareness of predisposing factors and also the avoidance and management of overweight and obesity in North Wollo, Northeast Ethiopia.MethodsFrom January 2022 to January 2023, A cross-sectional community survey was carried out with 1084 respondents aged 18 and above in North Wollo, Northeast Ethiopia. A multi-stage sampling technique was employed to recruit participants for the quantitative study, while a convenience sampling technique was employed for the qualitative study. A structured questionnaire that had been pre-tested was utilized to gather quantitative data, while qualitative data was collected using an interview. Body mass index was used to determine overweight and obesity. We employed ordinal logistic regression to examine the relationship between predictors and dependent variables. A p-value of 0.05 was statistically significant at 95% confidence.ResultsOverweight/obesity affected 21.3% of the population. Some risk factors were known to the majority of participants, such as excessive saturated fat consumption (52.4%) and a lack of regular physical activity (82.9%). However, a large proportion of respondents were not aware about family history (84.0%), age (57.9%), low intake of vegetables (63.0%), low intake of fruit (77.0%), low socioeconomic status (72.0%), smoking (82.5%), medication (58.0%), stress (82.9%), and lack of sufficient sleep (57.9%) were risk factors for overweight and obesity. The mass of respondents was aware of several methods for preventing overweight and obesity, such as limiting saturated fat consumption (52.4%) and engaging in regular physical activity (82.9%). However, a large percentage of respondents were unaware about getting enough sleep (57.9%), reducing stress (82.9%), managing medications (58.0%), quitting smoking (82.5%), having a good socioeconomic status (72.0%), high intake of fruit (77.0%), and high intake of vegetables (63.0%) could help prevent overweight and obesity. The majority of responders were aware that regular exercise helps with treatment strategies for fatness. However, the vast majority of responders were unaware that well-informed nutrition, weight loss medicine, and weight loss surgery were therapeutic options for overweight and obesity. High levels of stress (p = 0.000), female gender (p = 0.000), increasing age (0.000), physical inactivity (p = 0.000), low intake of fruit and vegetables (p = 0.000 and p = 0.012), smoking (p = 0.000), excessive use of saturated fat (0.043), and alcohol consumption (p = 0.000) all significantly increased the risk of over fatness.ConclusionAccording to the findings of this study, one-fifth of adults are overweight or obese. The majority of participants were unaware of typical risk factors for overweight/obesity, as well as prevention and treatment approaches for unhealthy habits and lack of physical activity.